Metallic glass-based nanocomposites : molecular dynamics study of properties - Sharma, Sumit, 1985- (Boca Raton : CRC Press LLC, 2019)
Metallic Glass-Based Nanocomposites: Molecular Dynamics Study of Properties provides readers with an overview of the most commonly used tools for MD simulation of metallic glass composites and provides all the basic steps necessary for simulating any material on Materials Studio. After reading this book, readers will be able to model their own problems on this tool for predicting the properties of metallic glass composites. This book provides an introduction to metallic glasses with definitions and classifications, provides detailed explanations of various types of composites, reinforcements and matrices, and explores the basic mechanisms of reinforcement-MG interaction during mechanical loading. It explains various models for calculating the thermal conductivity of metallic glass composites and provides examples of molecular dynamics simulations. Aimed at students and researchers, this book caters to the needs of those working in the field of molecular dynamics (MD) simulation of metallic glass composites.
Cover; Half Title; Title Page; Copyright Page; Dedication; Table of Contents; Preface; Editor; Contributors; Chapter 1: Introduction to Metallic Glasses; Chapter 2: Metallic Glass Nanocomposites: Their Properties and Applications; Chapter 3: Molecular Modeling of Metallic Glasses and Their Nanocomposites; Chapter 4: Predicting Thermal Conductivity of Metallic Glasses and Their Nanocomposites; Chapter 5: Study of Damping Behavior of Metallic Glass Composites at Nanoscale Using Molecular Dynamics; Chapter 6: MATLAB® Programming of Properties of Metallic Glasses and Their Nanocomposites; Index
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: Nanocomposites (Materials); Metallic glasses; TECHNOLOGY / Engineering / Chemical & Biochemical; TECHNOLOGY / Material Science